Market Reaction To Government Policy: Case The Tourism, Hotel, And Restaurant Sectors During Pandemic - Syamni, Ghazali; Rizal, Muhammad; Husaini; Terfiadi, Sari Yulis; Azzura (Jurnal Manajemen dan Keuangan, 2025)
This study examines the tourism, hotel, and restaurant sector's reaction to various government policies' announcements of COVID-19. This study used data from nine travel agencies, twenty-seven hotels, and eight restaurants collected from the Indonesian Stock Exchange and www.finance.yahoo.com. The limit was 10 days before and 10 days after the 7-event policy, with 140 days' worth of observations. This study found that abnormal returns were significantly negative when the government enforced community activities restrictions (PPKM) of the Micro policy in the restaurant industry. Besides that, in other events, the tourism, hotel, and restaurant sectors showed negative but insignificant statistical values. In addition, trading volume on the hotel, tourism, and restaurant indices shows different results between these indices. The hotel sector shows that when the government imposed the PSBB and PPKM there was a difference in the trading volume's statistical value, which was negative and significant except for PPKM-Zonation and PPKM-Emergency. The tourism sector shows negative and significant differences in trade volume values for PSBB and PPKM-Zonation, and PPKM-Emergency with positive differences. Finally, the restaurant sector found negative and significant differences during PSBB Transitional-I and positive trade volume differences during PPKM-Zonation